Early NK-cell and T-cell dysfunction marks progression to severe dengue in patients with obesity and healthy weight - Michaela Gregorova; Marianna Santopaolo; Lucy C. Garner; Rahma F. Hayati; Divya Diamond; Narayan Ramamurthy; Vi Thuy Tran; Nguyet Minh Nguyen; Kate J. Heesom; Vuong Lam Nguyen; Eben Jones; Mike Nsubuga; et al. (Nature Communications)
Abstract Dengue is a mosquito-borne virus infection affecting half of the world’s population for which therapies are lacking. The role of T and NK-cells in protection/immunopathogenesis remains unclear for dengue. We performed a longitudinal phenotypic, functional and transcriptional analyses of T and NK-cells in 124 dengue patients using flow cytometry and single-cell RNA-sequencing. We show that T/NK-cell signatures early in infection discriminate patients who develop severe dengue (SD) from those who do not. These signatures are exacerbated in patients with overweight/obesity compared to healthy weight patients, supporting their increased susceptibility to SD. In SD, CD4+/CD8+ T-cells and NK-cells display increased co-inhibitory receptor expression and decreased cytotoxic potential compared to non-SD. Using transcriptional and proteomics approaches we show decreased type-I Interferon responses in SD, suggesting defective innate immunity may underlie NK/T-cell dysfunction. We propose that dysfunctional T and NK-cell signatures underpin dengue pathogenesis and may represent novel targets for immunomodulatory therapy in dengue.